Stress Hormones: Emerging Targets in Gynecological Cancers - Chen, Guoqiang; Qiu, Lei; Gao, Jinghai; Wang, Jing; Dang, Jianhong; Li, Lingling; Jin, Zhijun; Liu, Xiaojun (Frontiers in Cell and Developmental Biology, 2021)
In the past decade, several discoveries have documented the existence of innervation in ovarian cancer and cervical cancer. Notably, various neurotransmitters released by the activation of the sympathetic nervous system can promote the proliferation and metastasis of tumour cells and regulate immune cells in the tumour microenvironment. Therefore, a better understanding of the mechanisms involving neurotransmitters in the occurrence and development of gynaecological cancers will be beneficial for exploring the feasibility of using inexpensive β-blockers and dopamine agonists in the clinical treatment of gynaecological cancers. Additionally, this article provides some new insights into targeting tumour innervation and neurotransmitters in the tumour microenvironment.